2016
DOI: 10.14503/thij-15-5353
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Enlargement within Months of Arteriovenous Fistula Creation in 2 Hemodialysis Patients

Abstract: Surgically created arteriovenous fistulae (AVF) for hemodialysis can contribute to hemodynamic changes. We describe the cases of 2 male patients in whom new right ventricular enlargement developed after an AVF was created for hemodialysis. Patient 1 sustained high-output heart failure solely attributable to the AVF. After AVF banding and subsequent ligation, his heart failure and right ventricular enlargement resolved. In Patient 2, the AVF contributed to new-onset right ventricular enlargement, heart failure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
(7 reference statements)
1
15
0
2
Order By: Relevance
“…Small studies or case reports have suggested that arteriovenous fistula may lead to development of high-output HF. 54 58 Arteriovenous fistula creation has also been reported in small studies to worsen right ventricular hypertrophy and pulmonary hypertension 54 , 59 and found to be associated with significant right ventricular dilatation and remodeling and an increased risk for development of incident heart failure. 60 On the other hand, other studies found a stabilization of kidney function after access creation.…”
Section: Cardiovascular Complications During Ckd G4+: Heart Failurementioning
confidence: 96%
“…Small studies or case reports have suggested that arteriovenous fistula may lead to development of high-output HF. 54 58 Arteriovenous fistula creation has also been reported in small studies to worsen right ventricular hypertrophy and pulmonary hypertension 54 , 59 and found to be associated with significant right ventricular dilatation and remodeling and an increased risk for development of incident heart failure. 60 On the other hand, other studies found a stabilization of kidney function after access creation.…”
Section: Cardiovascular Complications During Ckd G4+: Heart Failurementioning
confidence: 96%
“…The prevalence of pulmonary hypertension is much higher in the dialysis population and has been estimated at 17%–50% 12. However, there are a range of pathophysiological mechanisms that may explain this phenomenon, and it does not always follow that surgical fistula ligation is the correct treatment approach 13.…”
Section: Discussionmentioning
confidence: 99%
“…В последнее время в медицинской периодиче ской литературе появился ряд подобных публика ций в формате клинических наблюдений [14][15][16][17][18][19], однако все авторы отмечают отсутствие рандомизи рованных клинических исследований.…”
Section: Discussionunclassified